2016
DOI: 10.1136/archdischild-2016-311419
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in reducing group B Streptococcus disease in African settings

Abstract: Group B Streptococcus (GBS) is a leading cause of neonatal sepsis and meningitis in high-income settings and is associated with high rates of neonatal mortality and morbidity. There is now increasing evidence to suggest that there is a high GBS disease burden in resource-limited countries, and it is therefore critically important to identify suitable and practical preventive strategies. In Europe and North America, intrapartum antibiotic prophylaxis (IAP) has led to a dramatic reduction of early-onset GBS dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Thus, GBS surveillance programs would need to remain vigilant even after a vaccine becomes widely used. There are also significant challenges in resource-limited settings to consider prior to implementation (Reviewed in [132]). Regardless, it is clear that a vaccine would be the most effective means of reducing the global GBS burden of disease [133].…”
Section: Gbs Prevention and Therapeuticsmentioning
confidence: 99%
“…Thus, GBS surveillance programs would need to remain vigilant even after a vaccine becomes widely used. There are also significant challenges in resource-limited settings to consider prior to implementation (Reviewed in [132]). Regardless, it is clear that a vaccine would be the most effective means of reducing the global GBS burden of disease [133].…”
Section: Gbs Prevention and Therapeuticsmentioning
confidence: 99%
“…Since the 1970s, GBS has been reported as one of the leading causes of neonatal mortality and morbidity in the US [Dermer, et al, 2004] but it is increasingly recognised that the burden is greatest in low-to-middle income countries. In sub-Saharan Africa, for example, where up to 30 percent of women carry GBS asymptomatically, the incidence of invasive GBS disease in neonates has been reported to be up to 2.1 per 1000 livebirths, with case fatality rates ranging from 13 to 46 percent [Dagnew, et al, 2012;Heyderman, et al, 2016;Nishihara et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…In neonates, early-onset disease (EOD) in the first week of life typically presents as pneumonia or sepsis [Edmond et al, 2012, Nishihara et al, 2017. Late-onset disease (LOD) develops from 7 days to 3 months after birth and is frequently characterised by meningitis leading to chronic neurological damage, seizures, blindness and cognitive impairment in those that survive [Berardi et al, 2013;Nishihara et al, 2017]. The gastrointestinal tract is the reservoir for GBS and is the most likely source for maternal vaginal colonisation [Meyn et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent global estimate reported that, in 2015, GBS caused 90,000 deaths in infants aged younger than three months of age [1]; Africa accounted for 54% of estimated cases and 65% of all foetal/infant deaths. Maternal colonisation of GBS is an important source of infection in new-borns-up to 70% of infants born to colonised mothers are likely to be colonised themselves [2]. However, the microbial population genetics of mother-infant transmission of GBS remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%